Adolescent Weight Status and Related Behavioural Factors: Web Survey of Physical Activity and Nutrition - Kate E. Storey; Laura E. Forbes; Shawn N. Fraser; John C. Spence; Ronald C. Plotnikoff; Kim D. Raine; Linda J. McCargar (Journal of Obesity)
Purpose. To identify whether non-overweight students were different from their overweight or obese peers with respect to diet, suboptimal meal behaviours, and physical activity using a self-administered web-based survey. Methods. 4097 adolescents living in Alberta, Canada completed Web-SPAN (Web Survey of Physical Activity and Nutrition). Students were classified as overweight or obese, and differences were described in terms of nutrient intakes, physical activity, and meal behaviours. Results. Non-overweight students consumed significantly more carbohydrate and fibre, and significantly less fat and high calorie beverages, and had a higher frequency of consuming breakfast and snacks compared to overweight or obese students. Both non-overweight and overweight students were significantly more active than obese students. Conclusions. This research supports the need to target suboptimal behaviours such as high calorie beverage consumption, fat intake, breakfast skipping, and physical inactivity. School nutrition policies and mandatory physical education for all students may help to improve weight status in adolescents.